A taxonomy of resident engagement barriers in public open innovation - Sengewald, Timon; Riemer, Manuel; Posselt, Tim (Ongoing Research, Practitioners, Posters, Workshops, and Projects at EGOV-CeDEM-ePart 2024, 2024)
As governments at different levels - federal, state, and local - face complex societal challenges such as climate change or the transformation towards smart cities, efforts to engage civil society in decision-making and planning processes are increasing. However, not all citizens/residents are equally involved and broad participation is sometimes absent. Two bodies of literature are especially relevant to understanding potential barriers to participation that can lead to inequitable involvement in digital public decision-making: citizen/resident participation and public open innovation. Both must consider the reasons why residents may be unaware, unwilling, or unable to participate and find new ways to approach them, especially those who are marginalized and historically underrepresented. To assist practitioners and scholars in categorizing existing knowledge on barriers, we used a design sciences research approach to create a taxonomy for classifying resident engagement barriers in public open innovation. The final taxonomy consists of two dimensions and 14 characteristics. Public sector professionals, consultants and academics can use this taxonomy as a shared language to identify potential barriers and improve their engagement with residents.
CRIS-Team Scopus Importer:2024-08-16
Keywords: citizen participation; public open innovation barriers; resident participation barriers